Energy Harvesting Device Based on Spatial Electric Field in Substations - Hongwei Li; Ganrong Peng (Institute of Advanced Engineering and Science, 2014)
It is rich in electric field energy in high voltage substations while it is hardly collected and utilized. A novel energy harvesting device based on spatial electric field is presented in this paper, which is composed of capacitive energy collector and conditioning circuit. A simulation model of the energy collector is established to study the relationship between output voltage and its structural parameters and is verified by no-load tests. There are some restraining factors such as output voltage unstable in the traditional conditioning circuit. A new conditioning circuit is designed to overcome the problems and this new circuit is more effectively. This paper designs a new device to harvest the electric field energy within substations and it can provide broad potential use in the future.